Dermatofluoroscopy diagnostics in different pigmented skin lesions: Strengths and weaknesses. (12th July 2020) - Hofmann, Maja Ann; Keim, Ulrike; Jagoda, Agata; Forschner, Andrea; Fink, Christine; Spänkuch, Iris; Tampouri, Ioanna; Eigentler, Thomas; Weide, Benjamin; Haenssle, Holger A.; Garbe, Claus
Summary: Background: The melanin fluorescence of skin lesions is measurable with two‐photon excitation, a process termed dermatofluoroscopy, which has shown a shift from the green spectra in benign melanocytic lesions to the red spectra in melanoma. This study addressed the question as to which kind of pigmented lesions can be correctly diagnosed as melanin‐bearing malignant tumors. Methods: 476 pigmented lesions including 101 cutaneous melanomas were analyzed with dermatofluoroscopy, measuring the melanin fluorescence in a grid‐like fashion with a separation of measurement points of 0.2 mm. The results of the dermatofluoroscopy are presented as a diagnostic score with a cut‐off score of ≥ 28 for the diagnosis of melanin‐bearing malignant tumors, and were compared to the gold standard of histopathology. Results: A highly significant difference (p < 0.0001) between the diagnostic scores of different skin tumors was found. Dermatofluoroscopy scores showed the highest sensitivity for melanomas (92.1 %). Interestingly, most pigmented basal cell carcinomas (BCCs, 88.9 %) were diagnosed as melanin‐bearing malignant tumors. A higher sensitivity for the correct diagnosis was observed in older patients (≥ 53 years, p = 0.003), in patients with skin tanning (p = 0.025), and in patients with freckles during childhood (p = 0.046). Conclusions: Two‐photon fluorescence is an innovative technique for the diagnosis of pigmented skin lesions, and shows a high sensitivity for detection of melanomas and pigmented BCCs.